Mid-late Holocene vegetation history of the Argive Plain (Peloponnese, Greece) as inferred from a pollen record from ancient Lake Lerna. - Cristiano Vignola; Martina Hättestrand; Anton Bonnier; Martin Finné; Adam Izdebski; Christos Katrantsiotis; Katerina Kouli; Georgios C Liakopoulos; Elin Norström; Maria Papadaki; Nichola A Strandberg; Erika Weiberg; et al. (PLoS ONE, 2022)
This study provides a high-resolution reconstruction of the vegetation of the Argive Plain (Peloponnese, Greece) covering 5000 years from the Early Bronze Age onwards. The well dated pollen record from ancient Lake Lerna has been interpreted in the light of archaeological and historical sources, climatic data from the same core and other regional proxies. Our results demonstrate a significant degree of human impact on the environments of the Argive Plain throughout the study period. During the Early Bronze Age evidence of a thermophilous vegetation is seen in the pollen record, representing the mixed deciduous oak woodland of the Peloponnesian uplands. The plain was mainly used for the cultivation of cereals, whereas local fen conditions prevailed at the coring site. Towards the end of this period an increasing water table is recorded and the fen turns into a lake, despite more arid conditions. In the Late Bronze Age, the presence of important palatial centres modified the landscape resulting in decrease of mixed deciduous oak woodland and increase in open land, partly used for grazing. Possibly, the human management produced a permanent hydrological change at Lake Lerna. From the Archaic period onwards the increasing human pressure in association with local drier conditions caused landscape instability, as attested by a dramatic alluvial event recorded in the Pinus curve at the end of the Hellenistic Age. Wet conditions coincided with Roman times and favoured a forest regeneration pattern in the area, at the same time as we see the most intensive olive cultivation in the pollen record. The establishment of an economic landscape primarily based on pastures is recorded in the Byzantine period and continues until modern times. Overgrazing and fires in combination with arid conditions likely caused degradation of the vegetation into garrigue, as seen in the area of the Argive Plain today.